Structural origins of hemostasis and adaptive immunity. Issue 2 (26th September 2017) - Ware, Jerry; Varughese, Kottayil I.
Abstract: Essentials Structural similarities between platelet GPIb and immune proteins of jawless fishes are profiled. VLRs from lamprey eels and hagfish share a conserved domain arrangement with platelet GPIb. Leucine‐rich repeats flanked by disulfide loops are common between glycoprotein Ib and VLRs. Ancestors of the vertebrate lineage likely contain an ancient domain for hemostasis and immunity. Background: Adaptive immunity in jawless fishes is performed by a unique set of proteins termed variable lymphocyte receptors (VLRs). Here we compare the crystallographic structures of VLRs and the human primary hemostasis receptor, glycoprotein (GP) Ib. It has been estimated jawless fish vertebrates diverged from jawed vertebrates 500 million years ago. Identifying structural similarities provides insights into the origins of primary hemostasis and the unique adaptive immunity of jawless fishes. Methods: Three‐dimensional structures obtained from crystallographic data and primary sequences alignments are compared. The results focus on overall domain arrangement to include the structural roles of leucine‐rich repeats (LRRs), disulfide bond, and disulfide loop arrangements. Results: The crystal structures of human GPIb (GPIbαN) and jawless fish VLRs are made up of three common segments each. The N‐terminal cap and the C‐terminal cap are characterized by disulfide bonds conserved in both GPIbαN and VLRs. The body of each molecule consists of LRRs which varies depending on the number of LRRs present in each molecule. The stacking of the LRRs results in the formation of a concave surface which serves as a motif to build ligand‐binding specificity with the flanking regions. Conclusion: A comparison of VLR and GPIb structures reveals a phylogenetic trail of cellular differentiation contributing to mammalian hemostasis and jawless fish adaptive immunity. The results provide a structural basis to explain some of the interrelationships between hemostasis and immunity in vertebrates and potentially identifies a common ancestral motif linking hemostasis and immunity.